A theory of LBO activity based on repeated debt-equity conflicts - Malenko, Andrey; Malenko, Nadya (Journal of Financial Economics, 2015)
We develop a theory of leveraged buyout (LBO) activity based on two elements: the ability of private equity-owned firms to borrow against their sponsors׳ reputation with creditors and externalities in sponsors׳ reputations due to competition and club formation. In equilibrium, the two sources of value creation in LBOs, operational improvements and financing, are complements. Moreover, sponsors that never add operational value cannot add value through financing either. Club deals are beneficial ex post by allowing low-reputation bidders with high valuations to borrow reputation from high-reputation bidders with low valuations, but they can destroy value by reducing bidders׳ investment in reputation. Unlike leverage of independent firms, driven only by firm-specific factors, buyout leverage is driven by economy-wide and sponsor-specific factors.